Comprehensive Genomic Analysis of Bacillus thuringiensis Serovars: Core Genome Stability and Pan-Genome Expansion - Rasul, Md Saifur; Mohammad Mohi Uddin; Hossain, Sheikh Julfikar; Sarkar, Md Murshed Hasan; Md Abdullah Al Obaid (Bangladesh Journal of Microbiology, 2025)
Bacillus thuringiensis (Bt) is a bacterium widely known for its pesticidal properties, with numerous serovars exhibiting diverse ecological adaptations and pathogenic characteristics. In this study, we performed a comprehensive genomic analysis of 82 Bacillus thuringiensis serovars retrieved from GenBank, with the aim of investigating their core and pan-genome structures, genomic variation, and genetic relationships. Core and pan-genome analyses revealed a highly conserved core genome consisting of 3279 clusters, indicative of essential functional genes common to all studied serovars. In contrast, the pan-genome was vast, encompassing 25,447 clusters, underscoring the genetic diversity and adaptability of the species. Upset analysis of gene content revealed a range of overlap in genomic sequences among serovars, with shared core genes and strain-specific genes potentially explaining functional diversity. Average Nucleotide Identity (ANI) analysis showed substantial genetic divergence among serovars, with some exhibiting over 99% similarity, while others, such as Bacillus thuringiensis navarrensis, were more genetically distant. These findings enhance our understanding of the genomic architecture of Bacillus thuringiensis, providing insights into its genomic evolution. Bangla. J. Microbiol. 2025, Vol. 41, P: 1-10